The pivotal image findings of progressive multifocal leukoencephalopathy: A case report - Shou-De Ma; Chih-Wei Wei; Tai-Lin Huang; Chao-Hsin Wu; Shiang-Yu Chang (Tungs’ Medical Journal)
Progressive multifocal leukoencephalopathy (PML) is a rare disease associated with the reactivation of the JC virus, particularly in immunocompromised patients. A 60-year-old woman, who was on immunosuppressive therapy, presented with a sudden seizure and was diagnosed with PML based on magnetic resonance imaging (MRI) findings. Typically, PML appears on computed tomography scans as asymmetric focal zones of low attenuation in the periventricular and subcortical white matter, while MRI findings usually show multifocal demyelination in these areas. The imaging results in this case are consistent with the typical presentation of PML.